Analisa Terjadinya Duplikasi Nomor Rekam Medis Pada Pasien Rawat Inap Di RSU Madani Medan Tahun 2020 - Yudica Rosalina; Peberiwati Br Kabar (Journal of Innovative and Creativity (Joecy), 2025)
Duplication of medical record numbers is the existence of medical record numbers such as one medical record number owned by two patients and one patient has two medical record numbers. The impact of duplication of medical record numbers is that the contents of the medical record are not continuous, the medical record shelves will be full quickly, patients who have received new medical record numbers again if they are not known as duplicate numbers. The purpose of the study was to provide an overview of the implementation of medical record management and to find out about the occurrence of duplication of medical record numbers at RSU Madani Medan. This study is a descriptive study, namely describing data as a result of research. The method used in this study is the observation and interview method. Based on the results of the study on the double numbering of medical record files, it states that the medical record number is duplicated as many as 29 medical record numbers (29%) and the medical record number that is not duplicated is 71 medical record numbers (71%). The consequences of duplication of medical colleague numbering are: Services are hampered due to the length of time in searching for medical record files., Discontinuity of the contents of the patient's medical record. Information on the patient's medical history, examination results and treatment are not integrated, examinations and treatments are not maintained because they are not stored in one file. So it can be concluded that the numbering of medical record files will be achieved well if the officers really pay attention to their performance, are careful in working, and work professionally according to applicable procedures. The numbering used should use an online system, so as not to cause errors in the numbering of medical record files.